Dynamics of Permissive Parenting and the Formation of Social Behavior of Children Aged 4-5 Years - Susanti, Susi; Fitriyah, Qonitah Faizatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Parenting has a central role in shaping early childhood character and behavior. In a modern social context characterized by high mobility and economic pressure, many parents unknowingly apply a permissive parenting style that emphasizes children's freedom rather than controlling behavior. This condition raises new problems in the form of a decline in children's ability to regulate emotions and obey social rules. Although a number of previous studies have discussed the relationship between parenting and child development, there are still limited studies that examine the emotional and social dimensions of permissive parenting in children aged 4-5 years directly in the context of families and early childhood education institutions—suggesting that there is a research gap that needs to be bridged.This study aims to describe the real practice of implementing permissive parenting and analyze its influence on the social-emotional behavior of children aged 4-5 years. The research method uses a qualitative approach of the type of case study. Participants consisted of 12 people (4 parents, 4 early childhood teachers, and 4 children) who were selected purposively based on direct involvement in parenting interactions. Data were obtained through in-depth interviews, participatory observations, and field documentation, using semi-structured interview guides and child behavior observation sheets as the main instruments. Data analysis was carried out with the interactive model Miles, Huberman, and Saldaña, including the stages of data reduction, data presentation, and conclusion drawing that took place simultaneously.The results of the study show that permissive parenting often arises due to emotional factors (fear of disappointing children) and social factors (busy work, economic pressure, and "inbearable" culture). Children who are raised permissively tend to be confident and expressive, but experience obstacles in emotional control, obedience to rules, and social cooperation. These findings confirm that permissive parenting has a dual impact: it strengthens children's emotional freedom but weakens self-discipline and regulation. Therefore, this study recommends synergy between parents and PAUD institutions in balancing affection and discipline to support children's social-emotional development optimally.